An investigation of the neural substrates of mind wandering induced by viewing traditional Chinese landscape paintings - Wang, Tingting; Mo, Lei; Vartanian, Oshin; Cant, Jonathan S.; Cupchik, Gerald (Frontiers in Human Neuroscience, 2015)
The present study was conducted to investigate whether the calming effect induced by viewing traditional Chinese landscape paintings would make disengagement from that mental state more difficult, as measured by performance on a cognitive control task. In Experiment 1 we examined the subjective experience of viewing traditional Chinese landscape paintings vs. realistic oil landscape paintings in a behavioral study. Our results confirmed that, as predicted, traditional Chinese landscape paintings induce greater levels of relaxation and mind wandering and lower levels of object-oriented absorption and recognition, compared to realistic oil landscape paintings. In Experiment 2 we used functional Magnetic Resonance Imaging (fMRI) to explore the behavioural and neural effects of viewing traditional Chinese landscape paintings on a task requiring cognitive control (i.e., the flanker task)—administered immediately following exposure to paintings. Contrary to our prediction, the behavioural data demonstrated that compared to realistic oil landscape paintings, exposure to traditional Chinese landscape paintings had no effect on performance on the flanker task. However, the neural data demonstrated an interaction effect such that there was greater activation in the inferior parietal cortex (IPC) and the superior frontal gyrus (SFG) on incongruent compared with congruent flanker trials when participants switched from viewing traditional Chinese landscape paintings to the flanker task than when they switched from realistic oil landscape paintings. These results suggest that switching from traditional Chinese landscape paintings placed greater demands on the brain’s attention and working memory networks during the flanker task than did switching from realistic oil landscape paintings.